Bacteroides uniformis CECT 7771 alleviates inflammation within the gut-adipose tissue axis involving TLR5 signaling in obese mice - Fabersani Marrades, Mario Emanuel (2021)
This study investigated the immune mechanisms whereby administration of Bacteroides uniformis CECT 7771 reduces metabolic dysfunction in obesity. C57BL/6 adult male mice were fed a standard diet or a Western diet high in fat and fructose, supplemented or not with B. uniformis CECT 7771 for 14 weeks. B. uniformis CECT 7771 reduced body weight gain, plasma cholesterol, triglyceride, glucose, and leptin levels; and improved oral glucose tolerance in obese mice. Moreover, B. uniformis CECT 7771 modulated the gut microbiota and immune alterations associated with obesity, increasing Tregs and reducing B cells, total macrophages and the M1/M2 ratio in both the gut and epididymal adipose tissue (EAT) of obese mice. B. uniformis CECT 7771 also increased the concentration of the anti-inflammatory cytokine IL-10 in the gut, EAT and peripheral blood, and protective cytokines TSLP and IL-33, involved in Treg induction and type 2 innate lymphoid cells activation, in the EAT. It also restored the obesity–reduced TLR5 expression in the ileum and EAT. The findings indicate that the administration of a human intestinal bacterium with immunoregulatory properties on the intestinal mucosa helps reverse the immuno-metabolic dysfunction caused by a Western diet acting over the gut-adipose tissue axis.